Modification of screen printed carbon electrode with silicon nanowires for electrochemical detection of Hg(II) and Cd(II) in water - Mohamad Zain, Siti Nur Zawani (2015)
Water pollution resulting from heavy metal ions such as mercury and cadmium tends to have lethal effects on the environment and living organisms. This indicates the need for further research to develop on heavy metal sensors that are fast, potable and cost effective. In this research, Silicon Nanowires (SiNW’s), a 1-dimensional nanowire was used as a modifier for disposable screen printed carbon electrodes (SPCE) for detection of metal ions. The SiNW’s was characterized by different spectroscopic techniques and the application of SiNW’s on the surface of the electrode was found to increase the sensitivity of the electrode. The screen printed carbon electrode was modified by casting SiNW’s with 3-aminopropyl-triethoxysilane (APTES) onto the working electrode surface. The modified electrode (SiNW’s/APTES/SPCE) was then applied for Hg2+ and Cd2+ ion detection. Electrochemical studies using linear sweep stripping voltammetry performed with SiNW’s/APTES/SPCE were found to give a better response through the optimization of some analytical parameters. Concentration study of mercury with SiNW’s/SPCE gave linear calibrations and a detection limit value of 42.59 μg L−1 was achieved by applying deposition potential of -1.2V and deposition time of 160s. The electrode showed very good recovery indicating the accuracy of the method, while concentration study of cadmium with SiNW’s/SPCE gave a linear calibration with R2 = 0.994. A detection limit of 251.7 μg L−1 was also achieved by applying deposition potential of -1.2V and deposition time of 160s. Validation of the method with inductively coupled plasma-mass spectroscopy (ICP-MS) and atomic absorption spectroscopy showed very good correlation. This modified screen printed carbon electrodes with Silicon Nanowires (SiNW’s/APTES/SPCE) also found for simultaneously detection of Hg2+ and Cd2+ ions in the solution.